Lacustrine sediments and lichen transplants: two contrasting and complimentary environmental archives of natural and anthropogenic lead in the South Urals, Russia - Spiro, Baruch; Udachin, Valery; Williamson, Ben; Purvis, O. William; Tessalina, Svetlana; Weiss, Dominik (Springer Basel AG, 2013)
Lead (Pb) concentrations and isotope ratios of two different geochemical archives are compared; lake sediment cores and lichens (Hypogymnia physodes, naturally growing and transplanted) from a ca. 80 km-long transect centred on the Cu smelter and former mining town of Karabash, Ural Mountains, Russia. Lead concentrations in sediment cores from 10 lakes were generally low near their base and show an abrupt increase in their upper portions interpreted to coincide with the onset of large-scale smelting operations in 1910. Lead isotope ratios derived from 204Pb, 206Pb, 207Pb, 208Pb of the bottom layers differed significantly from those of the top. The top sediments have isotope ratios that show distinct end members, one of which was the stack dust from the Karabash smelter, which is similar to the Pb derived from ores from Sibay, a major mine in the Urals. The composition of the bottom sediment layers generally fall slightly off a mixing line between the top sediments and average Earth’s upper crust. Lichens transplanted from a reference site, as well as naturally growing lichens, sampled from southwest of the smelter have isotope ratios similar to those of the stack dust. Lichens to the northeast contained Pb from the smelter, but are increasingly influenced by other sources probably leaded petrol and local soils, and a signature derived from a source enriched in 207Pb. Vegetables collected from local kitchen gardens contained Pb from an additional atmospheric source, possibly coal.Our work confirms that: (1) Pb isotopes in lake sediments provide a long-term record of inputs and allows the characterisation of natural and anthropogenic sources; (2) Pb isotopes in lichens provide a short-term record of local and long-range atmospheric deposition at high spatial resolution and short time scales as they replace their Pb content within a few months; (3) determination of all four stable Pb isotopes is necessary for the identification of the sources of Pb and is extremely sensitive for discerning minor source signatures, even in an area with a dominant source such as a smelter. Particularly significant for the Karabash area is that ore-smelter-derived airborne Pb is a major component in the lake sediments and lichens but its contribution reaches insignificant levels ca. 40 km from the smelter.